THE EFFECTS OF COGNITIVE AND METACOGNITIVE LISTENING STRATEGIES ON STUDENTS’ ENGLISH LISTENING COMPREHENSION IN A MERCHANT MARINE POLYTECHNIC - Dyah Ratnaningsih (Widya Mandala Surabaya Catholic University, 2015)
This study aims to investigate whether the English listening strategies had the effect to English listening comprehension and also to see whether or not the application of the metacognitive listening strategies would produce higher English listening comprehension compared to the using of the cognitive listening strategies. In order to study this relationship, 60 (sixty) students of Deck Department in Politeknik Pelayaran Surabaya (Surabaya Merchant Marine Polytechnic) were choosen randomly and surveyed with thirty two structured questionnaires and a TOEIC listening test. The questionnaire was about a Listening strategy use developed by Lee (1997) and modified by Ho (2006) and also based on Vandergrift’s (1997, 2003) cognitive and metacognitive listening strategy classification. Statistical analysis of Linear Regression analysis, One-way Annova, Multiple regression analysis of Tukey HSD and Homogeneous subset test were used to know whether metacognitive listening strategies would give higher listening comprehension than cognitive listening strategies and also to see that metacognitive listening strategy would give more influence in listening comprehension that the cognitive listening strategies. The result indicated that the students who work with metacognitive listening strategies did not achieve better English listening comprehension than those who work with cognitive listening strategies and there was no effect in using the metacognitive and cognitive listening strategies in English listening comprehension. Key Terms: listening comprehension, listening strategies, cognitive strategies, metacognitive strategies, upper-level group, lower-level group.